Multidisciplinary Approach to Managing Infectious Diseases: The Roles of Health Assistants, Hospital Administration, Dentists, Nursing, Laboratory, and Pharmacy Technicians - Malaihi, Abdulrahman Yahya; Al-Otaibi, Ahmed bin Abdullah Sultan; Al-Zaidani, Hassan Abdullah; Alharthi, Abdullah Mubarak; Althobaiti, Mohammed Abdullah Eidhah; Al Gazlan, Wajd Naser; Almutairi, Abdulmajeed Ghazi M; Al-Balawi, Basma Salim Suleiman; Hawsah, Manal Ibrahim; Al Grash, Ashwag Hassan Abdurhman; Alshehri, Mohammed Ahmed; Alsaleh, Salem Homoud; et al. (Journal of Ecohumanism, 2024)
Infectious diseases are among the major challenges facing healthcare systems today and require an inter-multi-disciplinary approach to their prevention and management. It discusses how nursing, health administration, laboratory, and pharmacy teams put infection control into practice. Nurses perform hygiene and educate patients about the same. Health administrators ensure resource allocation and proper application of policies. Laboratory experts perform timely and appropriate diagnostics to facilitate treatment decisions, and pharmacy teams ensure that AMS initiatives are taken forward. It has been a very crucial contribution of all these teams combined in reducing healthcare-acquired infections and offering the best welfare to the patients. The findings call for increased collaboration with continued upgrades relentlessly in combating infectious diseases within healthcare settings.